Optimized scalable Byzantine fault tolerance algorithm - Sicheng HAN; Xiaorong ZHU; Xiuxian ZHANG (物联网学报)
Blockchain is a decentralized ledger which provides trust to both parties which distrust each other in a transaction.Blockchain initially served as the underlying framework that underpins bitcoin and has increasingly become a disruptive new technology in recent years.Consensus algorithm is one of the core technologies of blockchain.Without a consensus algorithm,the state consistency among distributed nodes cannot be achieved.The practical Byzantine fault tolerance (PBFT) algorithm was briefly introduced,which was a commonly used consensus algorithm in consortium blockchain.An optimized and scalable algorithm based on it was proposed.The improved algorithm mainly reduced the algorithm complexity and allowed consensus nodes to join and exit the system.Simulation results show that the improved algorithm can significantly reduce the transaction consensus completion time and the number of communication times between nodes,so as to increase the throughput of the whole system while supporting more nodes and reducing the system communication overhead and CPU computing resource consumption.